2021
DOI: 10.21037/gs-21-441
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of prognostic models in breast cancer: a narrative review

Abstract: Breast cancer is one of the most common malignant tumors in women, which is highly heterogeneous in molecular changes, cellular composition, therapeutic response, and clinical outcomes. Based on the transcriptional level, breast cancer can be divided into five intrinsic subtypes, luminal A (LumA), luminal B (LumB), HER2-enriched, basal-like, and normal-like (1). According to immunohistochemistry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…TNBC patients are not sensitive to endocrine and targeted therapies, and chemotherapy and radiotherapy are key therapeutic strategies ( 26 ). Studies have presented that receiving radiotherapy and chemotherapy after surgery has significant clinical value in improving the prognosis of patients ( 26 , 44 ). Recently, neo-adjuvant chemotherapy has gradually become the first choice of systemic therapy for TNBC, especially for those who have locally advanced tumors ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNBC patients are not sensitive to endocrine and targeted therapies, and chemotherapy and radiotherapy are key therapeutic strategies ( 26 ). Studies have presented that receiving radiotherapy and chemotherapy after surgery has significant clinical value in improving the prognosis of patients ( 26 , 44 ). Recently, neo-adjuvant chemotherapy has gradually become the first choice of systemic therapy for TNBC, especially for those who have locally advanced tumors ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies have applied conventional survival analysis methods, without considering the effects of competing events in the occurrence of events of interest, that is, deaths from nonbreast cancer reasons were not considered. Tumor-specific mortality in patients is likely to be overstated (24)(25)(26)(27). In order to identify and predict CSM risk for TNBC more accurately, we used a competing risk model to investigate 28,430 TNBC cases in the SEER database.…”
Section: Calculation Of Csm At Different Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prognostic model refers to the use of statistical methods to determine the quantitative relationship between the risk factors and the probability of clinical outcomes based on the patient's disease state. Breast cancer prognostic models can help clinicians and healthcare providers make more informed medical decisions on chemotherapy exemption (127). In recent decades, the most popular model is the COX proportional hazards model, which has been extensively studied in the fields of statistical learning (128).…”
Section: Prognosis Predictionmentioning
confidence: 99%
“…Clinical prediction models can combine multiple factors to achieve the individualized assessment of patient prognosis (9,10). Tan et al reported on the use of a nomogram (stromal atypia, mitoses, overgrowth and surgical margins; AMOS) to predict the RFS of PT patients based on histopathological features (11).…”
Section: Introductionmentioning
confidence: 99%